Welfare State and Tax Policy in a context of economic and budgetary crisis: the role of wealth taxation (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
A more stringent framework of Budget Discipline within the European Union has conditioned tax reforms passed in Spain over the last three years. These tax reforms have led to an inequitable distribution of the costs of the budgetary crisis. These costs burden more severely middle class workers, in opposition to betteroff sectors of society. From a tax justice point of view, wealth taxes should be reinstated, at least as long as Spain achieves the deficit target of 3 percent of GDP. Moreover, economic crisis and its causes have questioned the arguments that led to wealth taxes abolition.
Keywords: economic crisis; budget discipline; deficit; tax reform; tax justice; wealth taxes; inheritance taxes